2017
DOI: 10.1111/birt.12302
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of childbearing Medicaid beneficiaries engaged in care at Strong Start birth center sites between 2012 and 2014

Abstract: BackgroundVariations in care for pregnant women have been reported to affect pregnancy outcomes.MethodsThis study examined data for all 3136 Medicaid beneficiaries enrolled at American Association of Birth Centers (AABC) Center for Medicare and Medicaid Innovation Strong Start sites who gave birth between 2012 and 2014. Using the AABC Perinatal Data Registry, descriptive statistics were used to evaluate socio‐behavioral and medical risks, and core perinatal quality outcomes. Next, the 2082 patients coded as lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 19 publications
(21 reference statements)
1
52
0
Order By: Relevance
“…Ultimately, 2/3 of planned home births and 1/3 of birth center births were self-paid by the mother, compared to only 3% of hospital births. This suggests that, despite successful pilot projects (24), most current payment mechanisms are not structured to support out-of-hospital birth options for a large proportion of women seeking them. This lack of access to payment options for out-of-hospital births may prevent many women from choosing these births.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, 2/3 of planned home births and 1/3 of birth center births were self-paid by the mother, compared to only 3% of hospital births. This suggests that, despite successful pilot projects (24), most current payment mechanisms are not structured to support out-of-hospital birth options for a large proportion of women seeking them. This lack of access to payment options for out-of-hospital births may prevent many women from choosing these births.…”
Section: Discussionmentioning
confidence: 99%
“…The AABC birth center model provides enhanced primary maternity care that is integrated into the overall perinatal care system (Figure ). This midwifery‐led model (Figure ) includes structured relationship building, time‐intensive care, and individualized education, all of which have been demonstrated to improve outcomes for socially at‐risk communities …”
Section: Methodsmentioning
confidence: 99%
“…Studies of freestanding birth centers have consistently demonstrated safe, high‐quality care with fewer medical interventions during labor than usual care, while achieving lower cesarean birth rates . Neonatal outcomes have been similar to those of lower‐risk mothers in usual care …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…1 Birth center and midwifery-led care have been identified as a perinatal care model with the potential to help improve health outcomes for more women, including those experiencing disparities. [2][3][4][5] The recent publication of the national evaluation of the Strong Start for Mothers and Newborns Initiative revealed a dramatic reduction of preterm, low birth weight, and cesarean births for women participating in birth center care compared with women of similar risk levels in usual care. 6 Yet, there is little policy discussion about these significant findings or planning for wider implementation of birth center and midwifery-led care.…”
Section: Introductionmentioning
confidence: 99%